The Wages of Non-Blackness: Contemporary Immigrant Rights and Discourses of Character, Productivity, and Value - Nopper, Tamara K. (InTensions, 2011)
Drawing from W.E.B. Du Bois’ concept of the psychological wage of whiteness, this article explores how contemporary rhetoric promoted by immigrant rights advocates in the United States valorizes non-white immigrant workers in relationship to African Americans. Specifically, I examine moralized claims regarding immigrants’ character, productivity, and value as well as their contributions to the U.S. and global economy. I emphasize how this discourse echoes and draws upon managerial and capitalist perspectives of labor as well as anti-Black rhetoric regarding African Americans as lacking a work ethic, militant, xenophobic, and costly to society. Finally, I briefly consider whether the wage of non-Blackness differs from the wage of whiteness as well as the possibility of an ethical immigrant rights discourse.